Preparation of Colored Polymer Microspheres - Lei Wang; Weiting Ma; Shuheng Zhang; Mengke He; Ping Song; Hongying Wang; Xianxiao Song; Botian Li (Molecules)
Colored polymer microspheres have attracted significant attention in both academia and industry due to their unique optical properties and extensive application potential. However, achieving a uniform distribution of dyes within these microspheres remains a challenge, particularly when heavy concentrations of dye are used, as this can lead to aggregation or delamination, adversely affecting their application. Additionally, many dyes are prone to degradation or fading when exposed to light, heat, or chemicals, which compromises the long-term color stability of the microspheres. Consequently, the preparation of colored polymer microspheres with high stability continues to be a significant challenge. This review offers a comprehensive overview of the preparation techniques for colored polymer microspheres and their dyeing mechanisms, introducing the fundamental concepts of these microspheres and their applications in various fields, such as biomedicine, optical devices, and electronic display technologies. It further presents a detailed discussion of the different preparation methods, including physical adsorption, chemical bonding, and copolymerization. The advantages, limitations, and potential improvements of each method are explored, along with an analysis of the interactions between dyes and the polymer matrix, and how these interactions influence the properties of the microspheres, including their color uniformity, stability, and durability. Finally, the review discusses future perspectives on the development of colored polymer microspheres, highlighting the advancement of novel materials, innovations in preparation technology, and the exploration of potential new application areas.